Genome‐Wide Association Study of a Heart Failure Related Metabolomic Profile Among African Americans in the Atherosclerosis Risk in Communities (ARIC) Study. Issue 8 (11th August 2013) - Yu, Bing; Zheng, Yan; Alexander, Danny; Manolio, Teri A.; Alonso, Alvaro; Nettleton, Jennifer A.; Boerwinkle, Eric
<x xml:space="preserve">Abstract</x> Both the prevalence and incidence of heart failure (HF) are increasing, especially among African Americans, but no large‐scale, genome‐wide association study (GWAS) of HF‐related metabolites has been reported. We sought to identify novel genetic variants that are associated with metabolites previously reported to relate to HF incidence. GWASs of three metabolites identified previously as risk factors for incident HF (pyroglutamine, dihydroxy docosatrienoic acid, and X‐11787, being either hydroxy‐leucine or hydroxy‐isoleucine) were performed in 1, 260 African Americans free of HF at the baseline examination of the Atherosclerosis Risk in Communities (ARIC) study. A significant association on chromosome 5q33 (rs10463316, MAF = 0.358, P‐value = 1.92 × 10−10) was identified for pyroglutamine. One region on chromosome 2p13 contained a nonsynonymous substitution in N‐acetyltransferase 8 (NAT8) was associated with X‐11787 (rs13538, MAF = 0.481, P‐value = 1.71 × 10−23). The smallest P‐value for dihydroxy docosatrienoic acid was rs4006531 on chromosome 8q24 (MAF = 0.400, P‐value = 6.98 × 10−7). None of the above SNPs were individually associated with incident HF, but a genetic risk score (GRS) created by summing the most significant risk alleles from each metabolite detected 11% greater risk of HF per allele. In summary, we identified three loci associated with previously reported HF‐related metabolites. Further use of metabolomics technology will facilitate replication of these findings in independent samples.